La industria transgénica: Expropiación de la vida - González Cruz, Joaquín (Nómadas. Critical Journal of Social and Juridical Science, 2011)
The transgenic industry is today a serious problem with many edges, economic, political, social and biological. Obviously a bioethics problem that should not be free in the criminological analysis. Contemporary criminology should be doomed to study the multidimensional phenomena like this, since their actions or are involved certain types of offenses or conduct harmful to society, or may constitute a crime in itself.
Keywords: vernacular heath; transgenic; iatrogenic; conviviality; industrial growth